Zadovoljstvo državljanov Republike Slovenije z zdravstvenimi storitvami v Sloveniji - Zupanc Terglav, Barbara (Obzornik zdravstvene nege, 2019)
Introduction: Measurement of patient satisfaction with health services is an important development indicator of any healthcare system. Patient satisfaction is a significant and widely used indicator for measuring the quality of health services. The article focuses on the satisfaction of the citizens of the Republic of Slovenia with the current health system.Methods: Non-experimental descriptive sampling research method and a structured survey questionnaire as a metrics tool were used. The snowball sampling method was used. In total, 693 people responded to an online questionnaire, of which 488 answers were valid. The data were analysed using descriptive statistics, correlational analysis, factor analysis and linear regression analysis. Results: The respondents mostly value a friendly and respectful attitude of healthcare workers, and their availability to give first aid. However, the respondents negatively evaluated the time spent waiting for the medical examination in the waiting room, telephone unavailability, indifference to patients' personal situation and the short examination time with a doctor. Therefore, the most important variables that influence patient satisfaction are: the time spent waiting to be examined in the waiting room, sufficient time that doctors allocate to one patient, interest in personal matters, confidence in professional decisions made by the medical staff, patient involvement in their treatment and a sense of complete trust.Discussion and conclusion: Within the healthcare system, healthcare professionals can have a significant impact on patient satisfaction. A focus on high quality treatment and respectful communication increases the patients' trust in the healthcare system and in the professional decisions made by healthcare professionals, which may significantly impact the success of treatment.
Keywords: communication; health; health system; healthcare workers; javno zdravje; komunikacija; odnos; public health; relationship; satisfaction; trust; users; zadovoljstvo uporabnikov; zaupanje; zdravje; zdravstveni delavci; zdravstveni sistem